Social Contracts as Assets : A Possible Solution to the Time-Consistency Problem - Kotlikoff, Laurence J.; Persson, Torsten; Svensson, Lars E.O. (American Economic Review, 1987)
This paper presents a new solution to the time-consistency problem that appears capable of enforcing ex ante policy in a variety of settings in which other enforcement mechanisms do not work. The solution involves formulating a social contract, institution, or agreement that specifies the optimal ex ante policy. The social contract is effectively sold by succesive old generations to successive young generations, who pay for the social contract through the payment of taxes. Both old and young generations have an economic incentive to fulfill the social contract. For the old generation, breaking the social contract makes the social contract valueless, and the generation suffers a capital loss by not being able to sell it. For the young generation the economic advantage of purchasing the existing social contract exceeds its price as well as the economic gain from setting up the a new social contract.